Design and In silico Study of Amides Containing Heterocyclic Nitrogen as Potent Antituberculosis Agent - Wati, First Ambar; Afifah, Rizqi Nur; Wardana, Mohammad Wisnu (Universitas Pendidikan Mandalika, 2025)
Tuberculosis (TB) remains a serious infectious disease caused by Mycobacterium tuberculosis, representing a global health concern, especially owing to the increasing incidence of resistancy, including multidrug-resistant tuberculosis (MDR-TB). Among the potential therapeutic targets for new antituberculosis agents is enoyl-acyl carrier protein (ACP) reductase (InhA), an essential enzyme in the biosynthetic pathway responsible for the formation of vital components of the M. tuberculosis cell wall. This study aims to modify the compound N-(4-fluorobenzyl)pyrazine-2-carboxamide (1) by replacing the pyrazine group with N-(4-fluorobenzyl)-1H-pyrrole-2-carboxamide (4) and N-(4-fluorobenzyl)-1H-indole-2-carboxamide (5), and to evaluate their antituberculosis activity in silico, which has not been reported previously. Molecular docking was performed against the InhA receptor (PDB ID: 4TZK) using AutoDock 4.2.6 software. Method validation was performed using a gridbox with dimensions 30 × 24 × 16 and a grid center at coordinates 10,119; 32,370; 60,728; yielding an RMSD value of 1,16 Å. The docking results indicated that the three modified compounds provided lower binding energies than the control drugs, with compound 5 showing the lowest energy (-8.48 Kcal/mol), followed by compound 4 (-7.44 Kcal/mol) and compound 1 (-7.09 Kcal/mol). Pharmacokinetic predictions indicate that all three compounds comply with Lipinski’s Rule of Five and Veber’s filter, with high gastrointestinal absorption. The study results suggest that modified compound 5 has the strongest potential as an antituberculosis drug candidate and warrants further evaluation in vitro and in vivo.